Bahan Ajar Pembelajaran Cerita Pendek Berbasis Integrasi Keilmuan di Sekolah Menengah Pertama - Emah Khuzaemah; Hikmah Uswatun Ummi (Jurusan Tadris Bahasa Indonesia, 2020)
This study aims to develop short story teaching materials based on scientific integration. This study focuses on the analysis of needs and the development of teaching materials in junior high schools. Needs analysis was carried out using a questionnaire technique. Based on the results of the needs analysis, this scientific integration-based teaching material is urgently needed by Indonesian language teachers at MTs. The teaching materials developed are entitled